Application of digital-intelligent technologies in physical education: a systematic review - Qiying Zhong; Jiajun Jiang; Wenting Bai; Zhihua Yin; Ziyuan Liao; Xiaohui Zhong (Frontiers in Public Health, 2025)
BackgroundDigital-intelligent technologies (DIT), positioned at the convergence of artificial intelligence and digital transformation, have become pivotal to the modernization of physical education (PE). Although widely discussed within the context of Wisdom Education, their specific applications in PE have not been systematically synthesized. This study aimed to systematically review the scope, educational impacts, and implementation challenges of DIT in PE.MethodsA systematic review was conducted on 85 empirical studies published between January 2014 and November 2024. Following PRISMA guidelines, the review examined application scenarios, technological architectures, educational outcomes, and implementation barriers.ResultsDigital Intelligent technologies (DIT) have been adopted across all stages of PE, forming a closed-loop system that includes (a) intelligent instructional design, (b) real-time process visualization, and (c) data-driven evaluation and feedback. Key innovations involved adaptive learning platforms, virtual simulation tools, multimodal assessment systems, and health behavior monitoring. Challenges remain in algorithmic accuracy, data privacy, and unequal access to digital resources.ConclusionDigital-intelligent technologies (DIT) have reshaped physical education by enabling more intelligent, personalized, and data-informed instructional practices. To fully realize their potential, future efforts must prioritize algorithmic advancement, ethical safeguards, and the promotion of digital equity.